2019
DOI: 10.3390/medicina55080419
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelioma Mortality Rates in Greece for the Period 2005–2015 Is Increased Compared to Previous Decades

Abstract: Background and Objective: To present summary statistics regarding malignant mesothelioma (MM) mortality in Greece during the period 2005–2015 and compare it with previous decades, along with gender, age and geographical area analysis. Materials and Methods: The Hellenic Statistical Authority provided the data, which included all deaths for the period 1983 to 2015 that mentioned MM as the death cause in the corresponding death certificate. MM mortality rates have been calculated with respect to gender, age, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…On the other hand, asbestos is a natural nanomaterial that was widely used in buildings from the 1950s to the 1970s for its exceptional heat insulation [10] (Figure 1b), fire resistance, and sound insulation; however, inhalation exposure to asbestos nanoparticles has been shown to cause malignant tumors, such as pleural mesothelioma, and their use was prohibited in various countries [11][12][13][14]. Inhaled asbestos nanoparticles are believed to cause long-term inflammation in the lungs, malignant transformation of mesothelial cells as a result of their reactivity, and formation of malignant mesothelioma [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, asbestos is a natural nanomaterial that was widely used in buildings from the 1950s to the 1970s for its exceptional heat insulation [10] (Figure 1b), fire resistance, and sound insulation; however, inhalation exposure to asbestos nanoparticles has been shown to cause malignant tumors, such as pleural mesothelioma, and their use was prohibited in various countries [11][12][13][14]. Inhaled asbestos nanoparticles are believed to cause long-term inflammation in the lungs, malignant transformation of mesothelial cells as a result of their reactivity, and formation of malignant mesothelioma [15].…”
Section: Introductionmentioning
confidence: 99%
“…Entre as DRAs que acometeram os trabalhadores desta pesquisa, destaca-se a prevalência do MM, doença com rápida evolução, cujo período de latência depende do tempo de exposição, podendo ter uma latência de até 50 anos 21,27,47,48 . Observou-se, em um estudo realizado na Bélgica em 2015, que a mortalidade por MM foi maior entre os trabalhadores manuais em indústrias de amianto 22 .…”
Section: Discussionunclassified
“…Of the ARDs that affect the workers included in this research, it is worth noting the prevalence of MM, a rapidly evolving disease whose period of latency depends on time of exposure and may reach up to 50 years. 21 , 27 , 47 , 48 A study conducted in Belgium in 2015 showed that mortality for MM was higher among blue-collar asbestos workers. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Incidence across the EU is variable. National epidemiological studies in Poland analysing the incidence of asbestos-related diseases in the period of 1970-2015 revealed a decline in cases (20), whereas in Greece there was an increasing trend (21). A possible explanation is that the use of asbestos was banned at different times (22,23).…”
Section: Discussionmentioning
confidence: 99%